Perbandingan Daya Saing Crude Palm Oil Indonesia dengan Malaysia di Negara Tujuan Utama Ekspor: Comparison of the Competitiveness Crude Palm Oil of Indonesia with Malaysia in Main Export Destination Countries - Asrilis Saban; Tanti Novianti (Buletin Ilmiah Litbang Perdagangan, 2023)
This study aims to analyze and compare the competitiveness of Indonesian CPO with Malaysia in each of the main export destination countries. This study’s data type is monthly data for the export-import of Crude Palm Oil (CPO) with the code HS-151110. Competitiveness analysis between Indonesia-Malaysia CPO is calculated by RCA and MSI indicators. The development of Indonesia's CPO exports fluctuated from January 2020 to December 2021 with a negative development trend. During the period January 2020 to December 2021, Indonesian CPO has a comparative advantage in the Indian and Spanish markets, while Malaysian CPO has a comparative advantage in Italy and Kenya. Indonesian CPO has a larger market share in India and Spain and Malaysian CPO has a larger market share in Kenya, while in Italy the market share for Indonesian and Malaysian CPO is the same. Indonesia needs to increase CPO production and exports so that Indonesia’s CPO competitiveness and market share can be increased.